2023
DOI: 10.1002/ajmg.a.63409
|View full text |Cite
|
Sign up to set email alerts
|

Long term outcomes in children with trichohepatoenteric syndrome

Kwang Yang Lee,
Ronald Bremner,
Jane Hartley
et al.

Abstract: Trichohepatoenteric syndrome (THES) is a rare autosomal recessive disorder caused by mutations in either TTC37 or SKIV2L, usually leading to congenital diarrhea as part of a multisystem disease. Here, we report on the natural history of the disease for the largest UK cohort of patients with THES from 1996 to 2020. We systematically reviewed the clinical records and pathological specimens of patients diagnosed with THES managed in a single tertiary pediatric gastroenterology unit. Between 1996 and 2020, 13 pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Additional indicators of trichohepatoenteric syndrome (THES) include preterm delivery and intrauterine growth restriction (IUGR). THES patients typically exhibit a median gestational age of 35 weeks, as reported by Yang Lee et al, 2023 [ 7 ]. Comparing the two mutated genes, SKIC3 and SKIC2, a study by Bourgeois et al, 2018 revealed significantly greater birth weights and height percentiles for SKIC3 patients, with medians of 17.24 and 19.89, respectively [ 5 ].…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Additional indicators of trichohepatoenteric syndrome (THES) include preterm delivery and intrauterine growth restriction (IUGR). THES patients typically exhibit a median gestational age of 35 weeks, as reported by Yang Lee et al, 2023 [ 7 ]. Comparing the two mutated genes, SKIC3 and SKIC2, a study by Bourgeois et al, 2018 revealed significantly greater birth weights and height percentiles for SKIC3 patients, with medians of 17.24 and 19.89, respectively [ 5 ].…”
Section: Discussionmentioning
confidence: 96%
“…Hepatic involvement is also considered common, but it varies from transaminitis and hepatosplenomegaly to liver fibrosis [ 7 ]. It was noted that it is more frequently observed in patients with SKIC2 mutations (88%) than in those with SKIC3 mutations (51%) [ 5 ].…”
Section: Discussionmentioning
confidence: 99%